2020
DOI: 10.1073/pnas.2014468117
|View full text |Cite
|
Sign up to set email alerts
|

A highly immunogenic and effective measles virus-based Th1-biased COVID-19 vaccine

Abstract: The COVID-19 pandemic is caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) and has spread worldwide, with millions of cases and more than 1 million deaths to date. The gravity of the situation mandates accelerated efforts to identify safe and effective vaccines. Here, we generated measles virus (MeV)-based vaccine candidates expressing the SARS-CoV-2 spike glycoprotein (S). Insertion of the full-length S protein gene in two different MeV genomic positions resulted in modulated S protein ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
91
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(103 citation statements)
references
References 37 publications
(46 reference statements)
7
91
5
Order By: Relevance
“…These experiments showed significant reduction in replicating virus levels in the upper respiratory tract and the absence of detectable live virus in the lungs of animals upon two vaccinations with 10 μg of CVnCoV. This result is in line with previous observations in other respiratory viruses as well in SARS-CoV-2 challenge models in hamsters 30 and non-human primates 13,44 , where robust immune responses induced better protection in the lower than in the upper respiratory tract.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These experiments showed significant reduction in replicating virus levels in the upper respiratory tract and the absence of detectable live virus in the lungs of animals upon two vaccinations with 10 μg of CVnCoV. This result is in line with previous observations in other respiratory viruses as well in SARS-CoV-2 challenge models in hamsters 30 and non-human primates 13,44 , where robust immune responses induced better protection in the lower than in the upper respiratory tract.…”
Section: Discussionsupporting
confidence: 90%
“…On day 56, four weeks after the second vaccination, all animals were challenged with 10 2 TCID 50 /dose of SARS-CoV-2 featuring D614G. While this infection dose is low compared to other studies that employed doses of 2 x 10 3 to 2 x 10 6 TCID 50 30, 31, 32, 33, 34, 35, 36 , our results show robust levels of viral replication in the upper and lower respiratory tract (Figure 4) as well as typical weight loss for this model system 30, 31, 33 (Supplementary Figure 1) in the buffer control group.…”
Section: Resultsmentioning
confidence: 99%
“…We successfully rescued genectically stable rMV expressing high levels of S antigen from a strong early promoter of measles virus genome. This is in contrast to recently reported MV-based COVID-19 vaccine candidates 37 . Our lead candidate MV-ATU2-SF-2P-dER exibited a high viral titer (10 6 TCID 50 ) comparable to wild-type Schwarz MV strain and was genetically stable up to 10 passages while the previously reported rMV expressing the native S in the same promoter showed impaired growth 37 .…”
Section: Discussioncontrasting
confidence: 94%
“…This is in contrast to recently reported MV-based COVID-19 vaccine candidates 37 . Our lead candidate MV-ATU2-SF-2P-dER exibited a high viral titer (10 6 TCID 50 ) comparable to wild-type Schwarz MV strain and was genetically stable up to 10 passages while the previously reported rMV expressing the native S in the same promoter showed impaired growth 37 . One explaination could be that the 2P mutation helps a stable S protein expression therefore allowing rMV to grow better.…”
Section: Discussioncontrasting
confidence: 94%
“…During preparation of this manuscript, Hörner et al reported an rMeV-based SARS-CoV-2 vaccine candidate (58). They inserted the full-length S gene between the H and L genes, the last two genes of the MeV genome and therefore the S protein would be expressed at a lower level.…”
Section: Discussionmentioning
confidence: 99%